Anticariogeniceffect of Sambucuswilliamsii var. Coreana NAKAI (S. Williamsii) Extract on Against Streptococcus Mutans (Medico Legal Update, 2020)
Background/Objectives: The purpose of the present study was to assess the anticariogenic effects of Sambucuswilliamsii var. coreana NAKAI (S. williamsii) extract against Streptococcus mutans (S. mutans).Method/Statistical Analysis: S. williamsii purchased from Foodsynergy Co., Ltd. (Seoul, South Korea). Dried S. williamsii were then crushed and percolated in 70% ethanol, and concentrated S. williamsii extract was applied to S. mutans diluted to 5×105 CFU/ml at the concentrations of 0, 2.5, 5, 10, 20, and 30 mg/ml. Then the colony-forming units (CFUs) were evaluated at 6 and 24 h.Findings: The S. williamsii extract against S. mutans had an minimal inhibitory concentration (MIC) of 20 mg/ml and an minimum bactericidal concentration (MBC) of 30 mg/ml at 6 h, and an MIC of 10 mg/ml and an MBC of 20 mg/ml at 24 h. As the concentration of S. williamsii extract increased, the S. mutans was more clearly killed over time. The application of S. williamsii extract to S. mutans has an anti-dental-caries effect.Improvements/Applications: S. williamsii extract promotes oral health promotion by inhibiting the growth of S. mtans. It could be used as an effective oral anticariogenic agent.